The Mosaic of "Seronegative" Antiphospholipid Syndrome. (17th March 2014) - Conti, Fabrizio; Capozzi, Antonella; Truglia, Simona; Lococo, Emanuela; Longo, Agostina; Misasi, Roberta; Alessandri, Cristiano; Valesini, Guido; Sorice, Maurizio
Abstract : In the clinical practice it is possible to find patients with clinical signs suggestive of antiphospholipid syndrome (APS), who are persistently negative for the laboratory criteria of APS, that is, anti-cardiolipin antibodies (aCL), anti- β 2 -GPI antibodies and lupus anticoagulant. Therefore, it was proposed for these cases the term of seronegative APS (SN-APS). In order to detect autoantibodies with different methodological approaches, sera from 24 patients with SN-APS were analysed for anti-phospholipid antibodies using TLC immunostaining, for anti-vimentin/cardiolipin antibodies by enzyme-linked immunosorbent assay (ELISA), and for anti-annexin V and anti-prothrombin antibodies by ELISA and dot blot. Control groups of our study were 25 patients with APS, 18 with systemic lupus erythematosus (SLE), and 32 healthy controls. Results revealed that 13/24 (54.2%) SN-APS sera were positive for aCL (9 of whom were also positive for lysobisphosphatidic acid) by TLC immunostaining, 11/24 (45.8%) for anti-vimentin/cardiolipin antibodies, 3/24 (12.5%) for anti-prothrombin antibodies, and 1/24 (4.2%) for anti-annexin V antibodies. These findings suggest that in sera from patients with SN-APS, antibodies may be detected using "new" antigenic targets (mainly vimentin/cardiolipin) or methodological approaches different from traditional techniques (mainly TLC immunostaining). Thus, SN-APS represents a mosaic, in which antibodies against different antigenic targets may be detected.